Hubungan Antara Senam Asma Dengan Frekuensi Penggunaan Bronkodilator Pelega Pada Penderita Asma Di Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta - SETYAWAN, Anggi (2015)
Background : Asthma treatment includes pharmacological and nonpharmacological therapy, for nonfarmacologi asthma which recommended is asthma exercise. Asthma exercise that done regularly will increase the maximum volume of oxygen and can make a respiratory muscles stronger so that the power of heart muscle and other muscles become better. Objective : The research aims to find out the relationship between asthma excercise and the frequency of bronchodilators reliever on asthma patient in BBKPM Surakarta Method : The method was using observational analytic with cross sectional approach . The number of responden was 40 people (20 people to follow asthma exercise and 20 other). Sampling technique using simple random sampling. Measurement the frequency of bronchodilators reliever using Asthma Control Test questionnaire ( ACT ) , filling the questionnaire conducted by the respondent. Data were analyzed with Lambda Correlation test with SPSS 17.0 for Windows Result : The results showed the value of p = 0.017 ( r 0,526 ) that there is a significant relationship between asthma exercise with frequency of bronchodilators reliever. the strength of moderate correlation. The use of bronkodilator reliever on asma exercise group (10%) lower than group who do not follow asma exercise (37,5). Conclusion : There is a significant association between asthma exercise and frequency of bronchodilators reliever at the BBKPM Surakarta